Risk Factors for Long-Term Death After Medullary Infarction: A Multicenter Follow-Up Study - Zhang, Dao Pei; Liu, Xiang Zhe; Yin, Suo; Ma, Qian Kun; Yu, Meng; Zhang, Huai Liang; Wang, Xin Zhi; Zhang, Jie Wen (Frontiers in Neurology, 2021)
Background and Purpose: We investigated the risk factors for death in patients with medullary infarction (MI) during long-term follow-up. Methods: We retrospectively examined 179 consecutive patients (130 men, 49 women) who had clinical and MRI findings consistent with MI between February 2012 and January 2017 at three university hospitals. Long-term outcomes were assessed by telephonic interview. The clinical and radiological features and risk factors for poor outcomes (modified Rankin scale score ≥3, all-cause death) were analyzed. Results: Mean age of patients was 58.3±12.8 years (range, 25–87); mean follow-up period after stroke onset was 42.7±13.2 months (range, 24–78). Basilar artery (BA) stenosis >50% was more closely related to medial medullary infarction (MMI) than other types. There was greater frequency of ipsilateral vertebral artery hypoplasia (VAH) or V4AH and V4 occlusion in lateral MI than in other types. On rostro-caudal classification, middle (M)+dorsal (D) was most frequent, followed by the ventral (V)+M+D types. 21.2% patients showed poor long-term prognosis. Age≥65 years, recurrent stroke, dysphagia, >50% BA stenosis, and ventral MI were risk factors for poor long-term prognosis. All-cause mortality rate was 10.6%; age≥65 years, recurrent stroke, and dysphagia were risk factors for death in the long-term. Ventral MI and MMI+cerebellar infarction as well as stroke mechanism of artery-to-artery embolism were potential risk factors for death in the long-term. Pneumonia and recurrent stroke were major causes of death. Conclusions: Long-term poor outcomes of MI and all-cause mortality were not infrequent. Older age, recurrent stroke, and dysphagia were common risk factors for poor prognosis and death.